Do Governance and Sustainable Finance Affect Sustainability Disclosure? Evidence from Islamic Banks - Setyawan, Wahyu; Indriyani, I.; Asmar, Firli (Golden Ratio of Taxation Studies, 2026)
This study analyzes the influence of Good Corporate Governance and Sustainability Financial on Sustainability Reporting Disclosure of Islamic banks in Southeast Asia and the Gulf Cooperation Council region. Using panel data from 20 Islamic banks across both regions over the 2017–2023 period, a fixed effects regression model selected through Chow and Hausman tests was employed. The findings reveal that both Good Corporate Governance and Sustainability Financial have a positive and significant effect on Sustainability Reporting Disclosure. Good Corporate Governance emerges as a stronger driver of sustainability disclosure, indicating that banks with better governance structures are more transparent in reporting their sustainability practices. Sustainability Financial also contributes positively, though its effect is more modest, suggesting that financially sustainable banks tend to disclose more, but governance plays a more critical role in ensuring accountability. The study is limited to 20 banks over seven years with an R squared of 31.2%, indicating that other variables influence sustainability disclosure; future research should expand the sample, include additional control variables, and employ dynamic models. For practical implications, Islamic bank management should strengthen governance structures to enhance transparency and stakeholder trust, while regulators should implement policies that reinforce corporate governance frameworks, including the effectiveness of Sharia Supervisory Boards. From a social perspective, strong governance and financial sustainability contribute to greater transparency, which builds public trust and reinforces the legitimacy of Islamic banks as institutions committed to accountability and ethical operations. The originality of this study lies in simultaneously examining the direct effects of both Good Corporate Governance and Sustainability Financial on Sustainability Reporting Disclosure within a single analytical model and providing a comparative analysis across Islamic banks in Southeast Asia and the GCC region, offering empirical evidence that both governance and financial sustainability matter for sustainability disclosure.